Earth Magnetic Field Data Analysis For Earthquake Study - Selvakone, Sivanandini (Universiti Sains Malaysia, 2021)
Both International Real-Time Magnetic Observatory Network (INTERMAGNET) and Magnetic Data Acquisition System (MAGDAS) are groundbased magnetometer networks that have been developed to study the space weather. and monitor the geomagnetic variations. A MAGDAS-II type magnetometer was installed at Penang recently for seismic monitoring. Since the MAGDAS station is newly established, the sensitivity and reliability of the magnetometer had to be tested by comparing its data with geomagnetic data obtained from another well-established magnetometer system, INTERMAGNET. The INTERMAGNET station that was chosen for this study is Dalat, Vietnam. The variations of the geomagnetic components H, D, and Z obtained from both stations are analysed to verify the effectiveness of the newly installed MAGDAS magnetometer for seismic monitoring. Magnetometers used to observe the changes in Earth’s magnetic field for earthquake study. The change in the Earth’s magnetic field is caused by the increase in stress field within the lithospheric layers prior to an earthquake which can be recorded at geomagnetic stations of a specific distance. Therefore, this research also focused on examining the relationship between geomagnetic variations and earthquakes in Sumatra from 2015 to 2020. Hence, the behaviour of the geomagnetic components H, D, and Z before the earthquake must be monitored to identify a possible association between them. Any anomalous variation observed in the geomagnetic field can be used as a precursor for earthquakes to prevent casualties and damages.